Determination of the Composition of Metamorphic Rocks By Use of The Point Counter - Harrison, William Donald (My University, 1954)
A short history of micrometric analyses of rocks; the use of the point counter to determine the effect of orientation on the bulk composition of metamorphic rocks, the variations and limitations of the method with comparison of calculated analyses from the modes with an ordinary chemical analysis. The discrepancies lie within the range of experimental error. A quantitative interpretation by the use of statistics is offered.
Keywords: rocks, micrometric analyses, point counter, bulk composition, metamorphic rocks, Sillimanite Garnet Gneiss, Quartz